GRAMMATICAL METAPHOR AS FRAMEWORK ANALYSIS OF STUDENTS’ TRANSLATION OF DICSUSSION TEXT (A CASE STUDY OF ENGLISH DEPARTMENT’S STUDENTS IN PUBLIC UNIVERSITY INDONESIA UNIVERSITY OF EDUCATION) - Restu Surya Dinagara (Journal of English and Education, 2016)
This study focuses on investigating the procedures and methods of translating grammatical metaphors, introduced by Halliday (1985) and developed by Taverniers and Ravelli (2003), in students’ translation. This study was conducted in Indonesia University of Education, Bandung, taking six fifth semester students as the participants. In order to answer the research questions, this study employs a descriptive qualitative case study. The data were obtained from the collection of students’ translation of a discussion text from particular news website. The findings indicated that the translators need improvement in translating grammatical metaphors in terms of understanding the classification of metaphors, the congruent forms of metaphors, and relevant procedures of translating. Based on the text analysis, the students experienced some difficulties in translating grammatical metaphors in terms of adapting proper methods which led to mistranslating. Nevertheless, the translation produced by some students show relevant and equivalent translation. Thus, the translators need be taught explicitly about the grammatical metaphors and methods and procedures to translate the grammatical metaphors in order to produce relevant, equivalent, accurate, and faithful translation.